(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
By means of a literature review, this article aims to present basic aspects of the scientific and educational history of Brazil, from the colonial period to the present day. The major goal is to understand how science education has developed and consolidated as an important component of school curriculum and a formal field of research. Four phases were defined (1549–1800; 1800–1950; 1950–1970; 1970–today) to encompass the pedagogical, methodological, curricular, investigative, and legal processes that took place over these different periods in history. By offering a comprehensive overview of the national events that occured over time and giving educators and researchers who are interested in the topic a view of the past, the historical perspective chosen aims to contribute to the composition of the memory of science teaching.